2007
DOI: 10.1007/s11064-007-9330-0
|View full text |Cite
|
Sign up to set email alerts
|

Life-Long Hippocampal Neurogenesis: Environmental, Pharmacological and Neurochemical Modulations

Abstract: It is now well documented that active neurogenesis does exist throughout the life span in the brain of various species including human. Two discrete brain regions contain progenitor cells that are capable of differentiating into neurons or glia, the subventricular zone and the dentate gyrus of the hippocampal formation. Recent studies have shown that neurogenesis can be modulated by a variety of factors, including stress and neurohormones, growth factors, neurotransmitters, drugs of abuse, and also strokes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 122 publications
1
31
0
Order By: Relevance
“…This change is based mostly on facts accumulated recently, indi-Ryszard Pluta, Anna Bogucka-Kocka, Marzena Ułamek-Kozioł, Wanda Furmaga-Jabłońska, Sławomir Januszewski, Judyta Brzozowska, Mirosław Jabłoński, Janusz Kocki cating that neural stem/progenitor cells occupy two main regions, the subventricular zone of the lateral ventricles and the subgranular zone of the dentate gyrus in the hippocampus, where they give rise to neurons after birth [30,38,54,58]. Neurogenesis has been found in these brain areas in all mammalian species, including humans [9,30,38,54,58], and may serve to replace brain cells damaged by insults. Two discrete brain regions presented contain progenitor cells that are capable of differentiating into neuronal or glial cells.…”
Section: The Importance Of Hippocampal Neurogenesis In Postischemic Bmentioning
confidence: 99%
See 1 more Smart Citation
“…This change is based mostly on facts accumulated recently, indi-Ryszard Pluta, Anna Bogucka-Kocka, Marzena Ułamek-Kozioł, Wanda Furmaga-Jabłońska, Sławomir Januszewski, Judyta Brzozowska, Mirosław Jabłoński, Janusz Kocki cating that neural stem/progenitor cells occupy two main regions, the subventricular zone of the lateral ventricles and the subgranular zone of the dentate gyrus in the hippocampus, where they give rise to neurons after birth [30,38,54,58]. Neurogenesis has been found in these brain areas in all mammalian species, including humans [9,30,38,54,58], and may serve to replace brain cells damaged by insults. Two discrete brain regions presented contain progenitor cells that are capable of differentiating into neuronal or glial cells.…”
Section: The Importance Of Hippocampal Neurogenesis In Postischemic Bmentioning
confidence: 99%
“…Current research shows that neurogenesis can be modified by a variety of factors, including stress, neurohormones, growth factors, neurotransmitters and also stroke pathology [30]. In particular, hippocampal neurogenesis may play a role in modulation associated with neuropathology, such as cognitive disorders [38]. The stimulated neurogenesis at sites of brain damage may represent an attempt by the brain at self-regeneration after ischemia.…”
Section: The Importance Of Hippocampal Neurogenesis In Postischemic Bmentioning
confidence: 99%
“…Animal studies have already shown that acute or chronic stress can activate HPA axis and inhibit the cell proliferation in adult hippocampus (Warner-Schmidt and Duman, 2006;Paizanis et al, 2007). It has been shown that the psychosocial and physical stressors can inhibit the neurogenesis in various animal models and thus lead to decreased cell proliferation and survival (Joëls et al, 2007).…”
Section: Neurotrophic Mechanisms In Depressionmentioning
confidence: 99%
“…which is a traditional Chinese medicine widely used in clinical settings (Suzuk et al, 2004;Torkin et al, 2005). The main active fraction of Radix Glycyrrhizae is flavonoids, domestic and foreign scholars have conducted a number of studies on them (Surget et al, 2011;Paizanis et al, 2007). In this paper, the ethanol extract of Radix Glycyrrhizae is studied, and its inhibitory effect on SGC-7901 cells is explored.…”
Section: Introductionmentioning
confidence: 99%